Polyfactorial approach in the correction of cognitive impairment in patients with post-Covid syndrome - Chukhraiev, Nikolay; Zukow, Walery; Vladimirov, Alexander; Samosiuk, Nataliia; Chukhraieva, Olena (Journal of Education, Health and Sport, 2022)
The article discusses a multi-level polyfactorial approach in the correction of cognitive impairment in patients with post-Covid syndrome based on the combined use of cognitive-motivational correction of the psychological state and physiotherapeutic methods of treatment: multi-level magnetolaser therapy, advanced blood irradiation, transcranial neuroacoustic and light-pulse stimulation. According to the results of the analysis of the results of testing patients based on the Montreal scale for assessing cognitive functions before the start, after 6 and 12 procedures, as well as 4 weeks after the completion of rehabilitation in the first group, the average indicators of the level of cognitive functions changed from 18.2 to 21.4 points, in the second group from 17 to 26 points. Psychological testing using the psychometric tables of A. Beck and Spielberger-Hanin showed a decrease in the average level of depression after the procedures in the first group by 5.4±1.4 (from 27.5 to 22.1) points, the anxiety level by 4.9±0.3 (from 35.1 to 30.2), in the second group by 9.9±1.2 (from 27.3 to 17.4) and 8.2±0.4 (from 35.2 to 27.0), respectively. Additionally, it should be noted that the clients of the second group were more interested in conducting a second course. A multi-level approach in the medical rehabilitation of patients with post-Covid syndrome based on the use of psychological correction, magnetolaser effect on the projection of the liver, supravenous irradiation of blood and combined transcranial neuroacoustic and light-pulse stimulation in combination with endonasal breathing of a singlet-oxygen mixture in a magnetic field turned out to be the most effective for restoring cognitive functions.